Considering the effect of biomass energy consumption on economic growth: Fresh evidence from BRICS region. (July 2016) - Shahbaz, Muhammad; Rasool, Ghulam; Ahmed, Khalid; Mahalik, Mantu Kumar
Abstract: This paper investigates the relationship between biomass energy consumption and economic growth by incorporating capital and trade openness in production function for the case of BRICS countries. In doing so, unit root and cointegration tests have been used in order to examine unit root properties and long run relationship between the series for the period of 1991Q1–2015Q4. The results confirm the presence of long-run equilibrium relationship between the variables. Moreover, biomass energy consumption stimulates economic growth. Capital increments economic growth and trade openness spurs economic growth. The feedback effect exists between biomass energy consumption and economic growth. Trade openness Granger causes economic growth, capital and biomass energy consumption. The policy to adopt biomass as the primary source of renewable energy helps BRICS countries to achieve sustainable development goal in both short-run and long-run. However, the key innovative point of this study is to establish the sign for Granger causality test.